The Effect of The A Brusselian Model on The Achievement of Fifth-Grade Literary Students in Geography and The Development of Their Implicit Intelligence - Hashim Ahmed Obaid -Jubouri; Lujain Salem Mostafa Al-Shakarji (Indonesian Journal Publisher, 2025)
This research aims to investigate the (impact of the Presley model on the academic achievement of fifth-grade literary students in Geography and the development of their tacit intelligence). To achieve this, the researcher adopted an experimental methodology and formulated three null hypotheses. Equivalence was established between the study groups across several variables: chronological age (calculated in months), intelligence test scores, overall fourth-grade literary GPA in Geography, parental educational level, and tacit intelligence scale. The sample consisted of( 30) fifth-grade literary students from Granada High School for Boys representing the experimental group, and (30) fifth-grade students from Uthman ibn Affan High School for Boys forming the control group. The experimental group was taught using the Presley model, while the control group followed the conventional method. To fulfill the research objectives and hypotheses, two tools were prepared. The first was an achievement test in its final form, comprising 40 objective and essay items. Its face validity was confirmed by presenting it to a panel of experts and specialists. The researcher calculated the ease and discrimination coefficients for its items, and its reliability coefficient was 0.81. The second tool was a tacit intelligence scale consisting of 24 items. The validity and reliability of this scale were confirmed, with a reliability coefficient of 0.80. After selecting the sample members and establishing equivalence between the two groups across several variables, in addition to controlling internal and external validity and preparing lesson plans and research tools, the experiment was implemented. It began on Tuesday, October 3, 2024, and continued until Sunday, December 24, 2024 (thirteen weeks). Upon completion of the experiment, the researcher applied the two research tools to the students of both groups. After collecting and statistically analyzing the data using the t-test for two independent samples, the following results were obtained There was no statistically significant difference at the 0.05 level between the mean achievement scores of the experimental group taught using the Presley model and the mean achievement scores of the control group taught using the conventional method